Marketing social norms: Social marketing and the 'social norm approach'. Issue 1 (20th November 2012) - Burchell, Kevin; Rettie, Ruth; Patel, Kavita
ABSTRACT This paper is inspired by the observation that the social norm approach (SNA) to socially desirable behaviour change – that is, telling people about what lots of other people do – retains something of a Cinderella role among social marketing practitioners and academics. Thus, the objective of this paper is to bring the social norm approach to the attention of a wider – and specifically, marketing and social marketing – audience, in the hope that the practice, study and critical analysis of the approach can be widened and deepened. We begin this task by tracing the background of the social norm approach to its origins in psychology and social psychology and by discussing a number of typical social norm campaigns. Thereafter, we review four key characteristics of successful social norm campaigns. In our discussion, we return to a more theoretical discussion of how the social norm approach works, and we pose a number of questions that emerge from the paper. Copyright © 2012 John Wiley & Sons, Ltd.